Comparative study of one-sided factorizations with multiple software packages on multi-core hardware - Agullo, Emmanuel; Hadri, Bilel; Ltaief, Hatem; Dongarrra, Jack (Proceedings of the Conference on High Performance Computing Networking, Storage and Analysis, 2009)
The emergence and continuing use of multi-core architectures require changes in the existing software and sometimes even a redesign of the established algorithms in order to take advantage of now prevailing parallelism. The Parallel Linear Algebra for Scalable Multi-core Architectures (PLASMA) is a project that aims to achieve both high performance and portability across a wide range of multi-core architectures. We present in this paper a comparative study of PLASMA's performance against established linear algebra packages (LAPACK and ScaLAPACK), against new approaches at parallel execution (Task Based Linear Algebra Subroutines -- TBLAS), and against equivalent commercial software offerings (MKL, ESSL and PESSL). Our experiments were conducted on one-sided linear algebra factorizations (LU, QR and Cholesky) and used multi-core architectures (based on Intel Xeon EMT64 and IBM Power6). A performance improvement of 67% was for instance obtained on the Cholesky factorization of a matrix of order 4000, using 32 cores.